Study of compressive strength in artisanal adobe stabilized with cow manure, nopal sap, straw and bull blood - Ureña, M; Llumitasig, Sandy; Siza, A.; Coello, D. (Rev. Téc. Fac. Ing. Univ. Zulia, 2019)
Adobe has been used in construction since the first civilizations in the world, and to improve its mechanical properties, organic stabilizers were added. We studied the compressive strength of adobe cubic samples made with soil from the Sierra Region of Ecuador and organic stabilizers. Four organic stabilizers were studied: cow manure, nopal sap, straw and bull blood, which were added in specific percentages individually and in combination. Field and laboratory tests were carried out according to “Proyecto de actualización – versión 1 de la Norma Peruana E.080 de Noviembre 2013”. The results showed that the four organic stabilizers improve the compressive strength, having an increase from 0.5 to 13.1%. By using 10% of cow manure with 20% of bull blood the adobe compressive strength increased 13.1% in relation to the basic adobe.